La educación desde la perspectiva de la Escuela Austriaca de Economía - Lozano, Fernando Nogales Lozano (REVISTA PROCESOS DE MERCADO, 2012)
The current Central Planning of the Education is not only a consequence of intense political activism of the European social democracies (specifically in Spain), moreover is consequence of the absence of a clear ideological opposition by the socio-political liberalism. Therefore, the Austrian School of Economics has nowadays an obligation, rediscover and redefine the theoretical basis of freedom of education to deconstruct the current social democratic model of Central Planning of Education. There are two essential reasons: the first one, because it means a improvement for the full freedom of the private education market, more agile, less costly and more effective to coordinate the individual preferences to learning with the needs of the markets. The second one, because ethics demands defending an educational system based on liberal principles, without the meddling of a statist education. Key words: Education and Liberalism, Education and Socialism, evolutionary and anarcho-capitalism basis of the Austrian School for a free education. JEL Classification: I20, I21, I28. Resumen: La actual Planificación Central de la Educación no es solamente consecuencia del intenso activismo político de las sociales democracias europeas (muy en concreto de la española), también es consecuencia de la ausencia de una oposición ideológica clara por parte del liberalismo sociopolítico en general. Por tanto, reencontrar y en su caso redefinir las bases teóricas de la libertad de enseñanza, como es el caso de la Escuela Austriaca de Economía, para de-construir el actual modelo socialdemócrata de Planificación Central de la Educación, es hoy una exigencia. Dos son las razones fundamentales: la primera, por lo que significa de mejora para la plena libertad de los mercados privados de enseñanza, más ágiles, menos costosos y más eficaces para coordinar mejor las preferencias individuales de aprendizaje con las necesidades de los mercados. La segunda, por la eticidad que significa defender un sistema educativo basado en los principios liberales, de ausencia de coacción educativa estatista. Palabras clave: Educación y Liberalismo, educación y Socialismo, bases evolucionistas y anarcocapitalistas de la Escuela Austriaca para una educación en libertad. Clasificación JEL: I20, I21, I28.